Situations of serious and imminent danger: proposal of a methodology for preparedness in campsites - Cipriano Almeida (2012)
Camping parks are work, recreational and leisure locations of high risk when facing situations of serious and imminent danger, especially during peak season, not only due to higher climatic temperatures but also due to an increase in visitors, motorized vehicles and diverse materials and equipment. During this season a large number of undifferentiated personnel have to be contracted and employed in order to deal with the increase in work load caused by increased demand. These parks generate employment although only with seasonal characteristics. Within this view of prevention, the objectives of this study concentrates and centers itself on the evaluation of a work place in relation to risks leading to situations of serious and imminent danger as well as the elaboration and development of preventive and protective measures. So as to substantiate those objectives a thorough analysis of the current legislation was performed in order to identify the deviances to the norms which have been verified for this specific location of study. These deviances resulted not only from direct observation but also from the analysis of documentation, the map of the park as well as direct contact with management and staff. This research was established with the support of an observation guide and accompanied by photographs of some of the situations. A management system is proposed through which the vulnerability of all the visitors is reduced by devising organizational measures as well as informational and training sessions for the employees and visitors. The preventive measures proposed try to respond in accordance with the regulatory requirement of the employees' rights of access to information and training in relation to health risks and safety as well as the interventional measures in case of situations of danger and emergencies.